The Influence of Zakat, Infaq, and Alms on the Economic Empowerment of People in Indonesia - Didih Muhamad Sudi (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the effect of zakat, infaq, and alms on the economic empowerment of the people in Indonesia. The approach used is quantitative with multiple linear regression method using SPSS. Data were collected through questionnaires distributed to 100 respondents who are essential beneficiaries of zakat, infaq, and alms. The results showed that zakat has the most significant effect on economic empowerment compared to infaq and alms. This is due to the obligatory nature of zakat and its more structured distribution system through official institutions such as BAZNAS and LAZ. Meanwhile, infaq and alms still contribute to the economic welfare of the community, but the impact tends to be more consumptive than productive. In addition, this study also found that the use of productive funds and financial literacy have an important role in strengthening the impact of zakat, infaq, and alms on economic welfare mustahik. Therefore, a more optimal strategy is needed in the distribution and financial education for beneficiaries so that Islamic philanthropy funds can be used more productively. With better management, zakat, infaq, and alms can be effective instruments in reducing poverty and increasing the economic independence of the people in Indonesia.